Linking the Positivity Effect in Attention with Affective Outcomes: Age Group Differences and the Role of Arousal - Kappes, Cathleen; Streubel, Berit; Droste, Kezia L.; Folta-Schoofs, Kristian (Frontiers in Psychology, 2017)
Despite its assumed importance for emotional well-being, studies investigating the positivity effect (PE) in older adults’ information processing rarely tested its relationship with immediate or general affective outcome measures like emotional reactivity or emotional well-being. Moreover, the arousal level of the to-be-processed emotional stimuli has rarely been taken into account as a moderator for the occurrence of the PE and its relationship with affective outcomes. Age group differences (young vs. old) in attention (i.e., fixation durations using eye tracking) and subjective emotional reactions (i.e., pleasantness ratings) were investigated in response to picture stimuli systematically varied in valence (positive vs. negative) and arousal (low vs. high). We examined whether there is a link between age group differences in fixation durations and affective outcomes (i.e., subjective emotional reactions as well as emotional well-being). Older compared to young adults fixated less on the most emotional part in negative but not in positive low-arousing pictures. This age difference did not occur under high arousal. While age group differences in fixation duration did not translate into age group differences in subjective emotional reactions, we found a positive relationship between fixation duration on negative low-arousing pictures and emotional well-being, i.e., negative affect. The present study replicated the well-known PE in attention and emotional reactivity. In line with the idea that the PE reflects top-down-driven processing of affective information, age group differences in fixation durations decreased under high arousal. The present findings are consistent with the idea that age-related changes in the processing of emotional information support older adults’ general emotional well-being.